Zgoda(-y) na otrzymywanie newslettera z informacjami handlowymi drogą e-mailową - Mielniczuk, Martyna (Wydawnictwo C.H. Beck, 2018)
Do we give one consent or a few separate consents to receive an email newsletter in accordance with the applicable law? Do we express it/them in an explicit way or in an implied manner? Subscribing to the newsletter, what exactly do we agree to? On what basis do different recipients receive different content from the same sender? Are consents from consumers usually collected in accordance with the applicable law? The aim of this article is to indicate what consents should entrepreneurs collect if they want to send their newsletters to consumers and how should they collect them legally, bearing in mind the fact that they often profile their subscribers. In fact, many of them send the newsletter contrary to legal regulations of which the recipients are usually unaware of. The author discusses the most important issues related to the lawful sending of an email newsletter with commercial information in the light of provisions in regard to providing services by electronic means, telecommunications law and personal data protection.
Keywords: newsletter; commercial information; direct marketing; emailing; telecommunication terminal equipment; consent; personal data processing; legitimate interest pursued by the controller; profiling; electronic communication; Telecommunications Law; GDPR; providing services by electronic means